The abundance and diversity of Mollusks in mangrove ecosystem at coastal area of North Sulawesi, Indonesia - DEWI WAHYUNI K. BADERAN; MARINI SUSANTI HAMIDUN; RAMLI UTINA; SUKIRMAN RAHIM; RIFAL DALI (Society for Indonesian Biodiversity, 2019)
Abstract. Baderan DWK, Hamidun MS, Utina R, Rahim S, Dali R. 2019. The abundance and diversity of Mollusks in mangrove ecosystem at coastal area of North Sulawesi, Indonesia. Biodiversitas 20: 987-993. The study reported in this paper sought to analyze the abundance and diversity of Mollusks species in the coastal mangrove areas of Panango in North Sulawesi, Indonesia. Data collected in the study lent support to policy making in reducing the loss of marine biotic species in the coastal mangrove areas. Data collection used stratified-random sampling method (plot size was 10 m x 10 m) with three plots at each research station was used. Data analyzed by Odum formula for abundance, Shannon Wiener index for diversity and evenness index for evenness. The samples were collected from 2 research station covering 15 sampling sites. This research found 14 families of mollusks comprised of 11 gastropod families (21 species) and bivalve families (3 types). The highest of the relative density was found in Terebralia sp (24,24%), and the lowest relative density was obtained (1,52%) in the following species: Spondylus violaceus, Conus sp., Semiricinula turbinoides, and Faunus ater. The diversity index of mollusks species (Gastropoda and Bivalvia) at the observation station was classified as a high category, indicating by H’ >3,32 (Station I H’= 2,19 and Station II H’= 2,12). The evenness value in range 0,4<e<0,6. This indicates that the Mollusks species found in the research site had a medium amount. This study suggests a need to regulate mangrove areas of Panango for sustainable mangrove ecosystems management.